Brine shrimp lethality test on aqueous extract of Caesalpinia Sappan L. - Satya, Nathasya Angelia; Pradana, Dhigna Luthfiyani Citra; Kolib, Abdul; Aprilia, Citra Ayu (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2021)
Caesalpinia sappan L. is a plant in the Fabaceae family and has long been used as a medicinal plant. The wood of this plant contains active compounds including brazilin, flavonoids, tannins, alkaloids, saponins, and terpenoids, which have antioxidant, anti-inflammatory, antibacterial, antiviral, and anticancer properties. The purpose of this study was to find out the lethal concentration (LC50) in the aqueous extract of C. sappan wood using the brine shrimp lethality test (BSLT). LC50 is the concentration value of the compound that causes up to 50% death in larvae of Artemia salina. This study used four concentration treatments of 1000 ppm, 500 ppm, 100 ppm, and 50 ppm, and negative control repeated three times. Each concentration and the control negative used 10 A. salina larvae. The larval mortality was observed after 24 hours of treatment. An LC50 value of 322.54 ppm indicates an aqueous extract of C. sappan. Therefore, it was moderately toxic in this category.